Problems and Opportunities of Girls' Education (A Case Study Namobudda Kavre) - Acharya , Suresh (HISAN: Journal of History Association of Nepal, 2024)
Namobuddha is a significant Buddhist pilgrimage site located in Kavre District, Nepal. The main objective of this research was to understand the perception of people regarding problems and opportunities for girl’s education in this location. Interview, method schedule questionnaire, and observation method were applied to collect data from respondents. Data analysis was done through MS Excel. The development of the country is being presented with both opportunities and problems as a result of the recent major advancements in girls' education in Nepal. The government's dedication to advancing gender equality and international aid programs have made it easier for girls to access education. Positive results of these efforts include rising enrolment rates and shrinking the gender gap in primary and secondary education. Giving girls access to high-quality education gives them the knowledge and skills they need to make a significant contribution to society and end the cycle of poverty. Despite the advancements, obstacles still stand in the way of girls' education in Nepal being fully realized. Boys' schooling is frequently given priority over girls by sociocultural norms that are firmly anchored in traditional practices. Girls' access to school is still being hampered by early marriage, gender-based violence, and a lack of knowledge about the advantages of education. Girls' educational possibilities are disproportionately impacted by the poor infrastructure, scarce resources, and lack of trained teachers in remote rural locations. To overcome these obstacles and provide equal educational opportunities for everyone, the government, communities, and NGOs must work together.